Carbon steel passivity examined in solutions with a low degree of carbonation: The effect of chloride and nitrite ions - Valcarce, María Beatriz (2009)
The effect of nitrite ions as inhibitors against steel corrosion in carbonated and chloride-contaminated concrete pore simulating solutions (pH 9) is investigated. Various inhibitor dosages and two chloride contents are tested. The inhibition efficiency is evaluated measuring the corrosion potential, cyclic voltammograms, anodic polarization curves, pitting and repassivation potentials, polarization resistance and performing electrochemical impedance spectra, together with weight-loss measurements. Independently of the chloride content, when [NO2−] = 0.2 mol l−1, the inhibition efficiency reaches 99% and if pitting occurs, surface repassivation is possible. At high chloride contents, if inadequate dosages of inhibitor are used, the risk of pitting attack is high because Epit is close to the OCP. The [NO2−]/[Cl−] ratio is not an appropriated parameter to evaluate the inhibitor efficiency for varying chloride concentrations in a carbonated concrete. An optimal nitrite ions concentration ([NO2−] = 0.2 mol l−1) can be established as the most suitable parameter to guarantee the inhibitor efficiency in the different electrolytes studied.